Stiff man syndrome in a black girl. - Isaacs, H (1979)
A patient suffering from severe and continuous muscular spasms is presented. The condition has been classified as the stiff man syndrome and is the first case recorded of the condition in a young African girl. The electrophysiological, biochemical, histochemical, and ultramicroscopic aspects of this disorder have been studied. The spasm appears to be related to overproduction of brain noradrenaline.